(untitled) (Third Sector Social Economic Review, 2024)
Among the agricultural cooperatives, according to 2019 data, there are 281 agricultural sales cooperatives and more than 291 thousand partners of these cooperatives. Law No. 4572 on Agricultural Sales Cooperatives and Unions emphasizes that agricultural sales cooperatives can be established with at least 30 producers and that they play a role in the processing, sales and marketing of relevant agricultural products. In Turkey, the sales, distribution and marketing of these products such as hazelnuts, olives, olive oil, sunflowers, figs and cotton, which have industrial value and are important for consumers, are very important. Starting from this point, in this study, the effect of the image of MARMARABİRLİK, FİSKOBİRLİK and TARİŞ products, which are agricultural sales cooperatives, on consumer satisfaction and purchasing behavior was examined in the Kırşehir example. For this purpose, the survey was conducted with 396 participants using a 5-point Likert scale with a 95% reliability level. Correlation, regression, T-test and ANOVA tests were applied to the obtained data in the SPSS 22 package program in accordance with the hypotheses of the research. As a result of the analysis, it was concluded that the image of the agricultural sales cooperative products of the survey participants in the Kırşehir sample had significant effects on consumer satisfaction and purchasing behavior. Based on this result, the need for these cooperatives to take a greater role in sales and marketing and the importance of using various market and business tools for this is emphasized.